Sosialisasi Seribu Hari Pertama Kehidupan untuk Generasi Berkualitas menuju Indonesia Emas Tahun 2045 - Malik, Abdul; Utsman, Utsman; Mulyono, Sungkowo Edy; Arbarini, Mintarsih; Desmawati, Liliek (Universitas Negeri Semarang, 2021)
The purpose of this service activity is to increase the knowledge and understanding of community members of the importance of preparing and filling the first 1000 days of life (HPK) for children and mothers in Ngijo Village, Gunungpati District, Semarang City. The expected output target is one of the considerations as a basis for decision making in order to improve the quality of human resources in Ngijo Village. The method used is through face-to-face socialization. The results of the community service program in the form of the 1000 HPK socialization activities have been carried out well according to the plan that has been designed. This was evident from the positive response from the local government and the enthusiasm of the participants to take part in the socialization activities. The achievement of the results of this socialization is still not completely perfect, because there are participants who do not understand the integration between Posyandu and Posbindu, but cumulatively through community service evaluation activities, it is stated that there is an increase in changes in knowledge, understanding, behavior, and actions after participating in the 1000 HPK socialization activities.